Design of an automated smart device to facilitate home composting - Brizuela-Solís, José P. (2024)
Organic waste management was a significant global challenge, accounting for 37% of urban solid waste. Composty emerged as an innovative solution to facilitate home composting by automating key processes and reducing the required manual effort. This smart device detected and shredded waste, automatically mixed and aerated it, and continuously monitored composting conditions, providing real-time data via an app. The purpose of this research was to design and evaluate the effectiveness of Composty in managing organic waste in urban settings. The methodology included developing a functional prototype and conducting tests to measure its efficiency and ease of use. Key results indicated that Composty could significantly reduce the time and effort needed for composting, promoting greater adoption of this sustainable practice. Conclusions highlighted Composty's potential to transform organic waste management, contributing to landfill waste reduction and fostering more sustainable practices. This device not only simplified the composting process but also empowered users to take an active role in environmental protection. The research demonstrated that with Composty, composting could be accessible and efficient for any household, regardless of their knowledge.